Maqasid Shariah Implementation on Sukuk Analysis - Arsyi, Muhammad (Journal of Islamic Economics Literatures, 2023)
The main objective of this study is to conduct a bibliometric analysis and literature review on the implementation of Maqasid Sharia in the context of Sukuk from 2014 to 2023. Sukuk is a growing Islamic-based financial instrument that has a significant impact in the global financial market. Maqasid Sharia, or the purpose of sharia, has an important role in directing Islamic economic and financial practices. This study aims to explore how the concept of Maqasid Sharia has been applied in sukuk, as well as research trends relating to this topic during the period under study. Through bibliometric analysis and literature review, this paper will provide insight into the development of research related to Maqasid Sharia and sukuk during the period, as well as provide a better understanding of the contributions and challenges in implementing Sharia principles in sukuk financial instruments. This research is expected to contribute in broadening the understanding of the role of Maqasid Sharia in sukuk development and provide direction for further research in this area.